2015
DOI: 10.1111/ibi.12252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decreased anthropogenic food availability on an opportunistic gull: evidence for a size‐mediated response in breeding females

Abstract: Some opportunistic vertebrates exploit, and may largely rely upon, food generated by human activities. Better understanding the influence of this additional anthropogenic food on species' ecology would inform sustainable waste management. In the Balearic Archipelago of Spain, closure of an open‐air landfill site provided an experimental setting to measure the effect of removing anthropogenic food on the average body mass, breeding parameters and body condition of opportunistic Yellow‐legged Gulls Larus michahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 67 publications
(116 reference statements)
3
58
1
1
Order By: Relevance
“…Nevertheless, when food is in very short supply it can even affect body mass and local adult survival in long-lived seabirds (Oro and Furness 2002). This appears to be the case for our population, given the recorded drop in YLG body condition (Steigerwald et al 2015) along with a slight decrease in local survival rates after landfill closure. Gulls usually form spatially structured populations and given that previous studies have shown that dispersal occurs following environmental perturbations (Oro et al 2004, Ferna´ndez-Chaco´n et al 2013, we suggest that food limitation has triggered not only mortality but also permanent emigration (through breeding dispersal) to neighboring populations (Bosch 2000, Oro 2003.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Nevertheless, when food is in very short supply it can even affect body mass and local adult survival in long-lived seabirds (Oro and Furness 2002). This appears to be the case for our population, given the recorded drop in YLG body condition (Steigerwald et al 2015) along with a slight decrease in local survival rates after landfill closure. Gulls usually form spatially structured populations and given that previous studies have shown that dispersal occurs following environmental perturbations (Oro et al 2004, Ferna´ndez-Chaco´n et al 2013, we suggest that food limitation has triggered not only mortality but also permanent emigration (through breeding dispersal) to neighboring populations (Bosch 2000, Oro 2003.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies on gulls found severe impacts on breeding performance under different levels of food availability (Pons 1992, Pons and Migot 1995, Oro 1996. Particularly, our colony suffered a significant decrease in breeding performance (clutch size and egg volume) after landfill closure (Steigerwald et al 2015). Moreover, Steigerwald et al (2015) suggested that a dietary switch, which we confirmed, might not have been sufficient to fully cover the energy requirements of the local population.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations